2021
DOI: 10.1111/adb.13086
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐132 is involved in morphine dependence via modifying the structural plasticity of the dentate gyrus neurons in rats

Abstract: Repeated morphine exposure has been shown to induce neuronal plasticity in reward‐related areas of the brain. miR‐132, a CREB‐induced and activation‐dependent microRNA, has been suggested to be involved in the neuronal plasticity by increasing neuronal dendritic branches and spinogenesis. However, it is still unclear whether miR‐132 is related to morphine dependence. Here, we investigate whether miR‐132 is involved in morphine dependence and whether it is related to the structural plasticity of the dentate gyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, Jia and colleagues recently carried out another study, in which it was noted that in vitro morphine exposure (for 24 h) promotes the differentiation of N2a cells that express the µ-opioid receptor via the upregulation of miR-132 expression. They also observed that in vivo morphine dependence was clearly associated with increased miR-132 expression and neuronal structural plasticity in the DG neurons of rats [33]. These findings again demonstrated a specific link between miR-132 expression and changes in neuronal structure and function upon opioid exposure.…”
mentioning
confidence: 79%
“…Interestingly, Jia and colleagues recently carried out another study, in which it was noted that in vitro morphine exposure (for 24 h) promotes the differentiation of N2a cells that express the µ-opioid receptor via the upregulation of miR-132 expression. They also observed that in vivo morphine dependence was clearly associated with increased miR-132 expression and neuronal structural plasticity in the DG neurons of rats [33]. These findings again demonstrated a specific link between miR-132 expression and changes in neuronal structure and function upon opioid exposure.…”
mentioning
confidence: 79%
“…This observation is consistent with previous reports describing a similar pattern of long-term morphine-induced structural plasticity in several regions belonging to the reward circuit [ 2 , 5 , 12 , 45 ]. However, more recent studies have highlighted some contradictory data depicting an opposite effect, especially in the NAc, the orbital prefrontal cortex and the dentate gyrus of the hippocampus [ 13 , 14 , 15 , 46 ]. These differences could be attributed to several factors, such as the paradigm of drug administration, the animal sacrifice time point, the brain region analyzed, or even the cell type studied.…”
Section: Discussionmentioning
confidence: 99%
“…A combined in vivo/in vitro study by Jan and coworkers [142] revealed that morphine dependence increased the expression of miRNA132-a CREB-induced and activationdependent microRNA-in the dentate gyrus of rats promoting dendritic branching and spinogenesis; in turn, the inhibition of miRNA132-3p but not miRNA132-5p relieved mor-phine withdrawal symptoms. Consistently, in an in vitro model of µ-N2a cells that stably express MOR receptor, 24 h morphine treatment up-regulated miRNA132, promoting their differentiation [142]. Thus, miRNA132 in the hippocampus participates in morphine dependence modifying neuronal plasticity.…”
Section: Epigenetic Mechanisms and Targets In Drug Addictionmentioning
confidence: 99%
“…Morphine withdrawal symptoms miRNA132-3p - [142] Reconsolidation of cocaine-associated memory circTmeff-1 miRNA206 BDNF [155] BDNF: Brain-derived neurotrophic factor; Btg2: BTG anti-proliferation factor 2; Cd69: CD69 molecule; Cldn11: claudin 11; DRD2: dopamine D2 receptor; REST: RE1-silencing transcription factor; Tmeff-1: tomoregulin-1; -: not tested.…”
Section: Ncrna Targets Referencesmentioning
confidence: 99%